Retrospective Validation of a Structure-Based Virtual Screening Protocol to Identify Ligands for Estrogen Receptor Alpha and Its Application to Identify the Alpha-Mangostin Binding Pose - Agustina Setiawati; Florentinus Dika Octa Riswanto; Sri Hartati Yuliani; Enade Perdana Istyastono (Indonesian Journal of Chemistry, 2014)
The publicly available enhanced data of ligands and decoys for estrogen receptor alpha (ERα) which were recently published has made the retrospective validation of a structure-based virtual screening (SBVS) protocol to identify ligands for ERα possible. In this article, we present the retrospective validation of an SBVS protocol using PLANTS molecular docking software version 1.2 (PLANTS1.2) as the backbone software. The protocol shows better enrichment factor at 1% false positives (EF1%) value and the Area Under Curve (AUC) value of the Receiver Operator Characteristic (ROC) compared to the original published protocol. Moreover, in all 1000 iterative attempts the protocol could reproduce the co-crystal pose of 4-hydroxitamoxifen in ERα binding pocket. It shows that the protocol is not only able to identify potent ligands for ERα but also able to be employed in examining binding pose of known ligand. Thence, the protocol was successfully employed to examine the binding poses of α-mangostin, an ERα ligand found in the Garcinia mangostana, L. pericarp.